Subordinate kinship : families living with incarceration - Wood, Victoria Jane (2008)
This thesis explores the relationships and kinship practices of women, in the North of England who have a husband or partner in prison. In particular it focuses on how kinship in the context of incarceration is subordinate. The study is addressed from the perspective of the mothers of prisoners' children who are the wives and partners of prisoners. The study derives from qualitative ethnographic research which was undertaken between May 2004 and September 2005. During this time participant observations at the Visitors' Centres of a category B male local prison and a High Security Estate prison were conducted as a means of gaining valuable insights into the way in which the rules and regulations of the prison establishment govern the different forms of contact between prisoners and their families. This was supported by unstructured in-depth interviews with eleven women who were the wives or partners of male prisoners with the aim of collecting more detailed biographical case study data, focusing on their experiences. The issues which this thesis addresses and which derived from the research data collected were questions concerning what is the relationship between the family and the prison; how the tensions between exacting justice and the families welfare impact on health and well-being of mothers and their perception of the impact on their children, the effect of incarceration on kinship practices, and the extent to which incarceration influences the lives of these women beyond the institutional setting, with emphasis placed on their relationships and social networks. The theoretical focus of the study is orientated towards a contextualisation of the family and the use of imprisonment in both a contemporary and historical context, drawing, in particular, on the work of Foucault and his ideas concerning discipline and surveillance. The themes used revolve around, experiences of separation, notions of exchange and gift giving, ideas of the Visitors' Centre as a liminal space, secondary prisonization, and stigma. The conclusions drawn bring these ideas together to show how 'a subordinate kinship' is manifest in this context.EThOS - Electronic Theses Online ServiceGBUnited Kingdo